Effect of pressure on the Maillard reaction between ribose and cysteine in supercritical carbon dioxide - Xu, H.,China Agricultural Univ., Beijing (China). Coll. of Food Science and Nutritional Engineering; He, W.,China Agricultural Univ., Beijing (China). Coll. of Food Science and Nutritional Engineering; Liu, X.,China Agricultural Univ., Beijing (China). Coll. of Food Science and Nutritional Engineering; Gao, Y.,China Agricultural Univ., Beijing (China). Coll. of Food Science and Nutritional Engineering (Czech Journal of Food Sciences, 2010)
An aqueous ribose-cysteine model system, heated at 140 deg C under supercritical carbon dioxide (SC-CO2) and supercritical nitrogen (SC-N2), was investigated with emphasis on the formation of volatile compounds. In general, SC-CO2 facilitated the overall intermediates accumulation while suppressing the advanced stage of browning. 3-Methyl-1, 2-dithian-4-one increased with increasing SC-CO2 pressure, and was always more concentrated than in the case of SC-N2-treatment. The formation of thiols, disulfides, and formyl substituted thiophenes was also promoted in SC-CO2-treated reaction products, while the effect of high pressure on the individual components followed different patterns. The reversible pH decrease and reinforced acid-base catalysis of 2, 3-enolisation by SC-CO2 could be attributed to the decreased browning and higher amounts of most intense meaty aromatic compounds.